Navigating Work-Life Integration, Legal Issues, Patient Safety: Lessons for Work-Life Wellness in Academic Medicine: Part 1 of 3 - Hartwell, Jennifer; Barach, Paul; Gunter, Tracy; Reed, Kyra; Kelker, Heather; Welch, Julie; Olson, Kristine; Harry, Elizabeth; Meltzer-Brody, Samantha; Quinn, Mariah; Ferrand, Jennifer; Kiely, Sharon; et al. (Kansas Journal of Medicine, 2023)
In this series of three manuscripts, we will explore real-life scenarios encountered by clinicians, learners, and researchers in healthcare, which challenge our assumptions and our understanding of how to navigate issues as diverse as mental health, racial diversity, gender discrimination, imposter syndrome, and substance use disorder.